The distribution of HLA‐DRB3 alleles among HLA‐DRB1*03:01‐positive haplotypes. (30th July 2018) - Stingl Jankovic, K.; Grubic, Z.; Jakupic, J.; Burek Kamenaric, M.; Maskalan, M.; Zunec, R.
Abstract : HLA‐DRB3 allelic polymorphism on HLA‐DRB1*03:01 ‐positive haplotypes was investigated among 104 cadaveric donors typed for HLA‐A, ‐B, ‐DRB1, and ‐DRB3. Only HLA‐DRB3*01:01:02 and ‐DRB3*02:02:01:01 alleles were detected among HLA‐DRB1*03:01‐ positive individuals and their distribution depended on HLA‐B*08 presence: nearly all HLA‐B*08 ‐positive samples carried DRB3*01:01:02, while HLA‐DRB3*02:02:01:01 was more frequent among HLA‐B*08 ‐negative subjects.